Enhancement of kaolin Clay Soil for Civil Engineering Application Using Rice Husk Ash and Sawdust Ash Geopolymer Cements - Anigilaje Bunyamin Salahudeen; Nana Sunday Kpardong; Patience Mark Francis (Nigerian Journal of Technological Development, 2023)
These days, good quality road construction materials are scarce and their haulage to the construction site is expensive. When unsuitable materials are encountered during flexible pavement construction, the most technical and economical option is always to improve them to meet design standards. One of these deficient materials mostly encountered in tropical regions is kaolin clay soils. Cement and lime that are traditional deficient soil improvement agents are on high demand therefore have kept the cost of engineering construction financially high. Thus, the use of agricultural wastes such as sawdust and rice husk as alternative construction materials will considerably reduce the cost of construction and as well mitigate the environmental hazards caused by the wastes and cement production. This study investigated and compared the performance of rice husk ash (RHA) and sawdust ash (SDA) geopolymer cements in improving the geotechnical properties of kaolin clay soil used for flexible pavement construction. All laboratory experimental tests were carried out in accordance with British Standard (BS) 1377 and BS 1924 for natural and modified kaolin clay soil samples respectively. Soil samples were mixed with geopolymer cement at stepped concentrations of 0, 4, 8, 12, 16 and 20% by dry weight of soil. Results indicated that the plasticity index value of the natural kaolin clay of 18.52% was reduced to 7.24% at 20% RHA geopolymer cement content. The unconfined compressive strength of the natural soil was improved by 600 and 400 % by RHA and SDA geopolymer cements respectively. It was concluded that the use of up to 20% RHA and SDA geopolymer cements can efficiently and eco-friendly improve kaolin clay for flexible pavement foundation purpose